Metal-organic frameworks for hepatocellular carcinoma therapy and mechanism - Feng, Yingqi; Wu, Wei; Li, Muzi (Frontiers in Pharmacology, 2022)
In recent years, metal organic frameworks (MOFs) have attracted increasing attention in cancer therapy, because they can enhance the anticancer efficacy of photodynamic therapy (PDT), photothermal therapy (PTT), photoacoustic imaging, and drug delivery. Owing to stable chemical adjustability, MOFs can be used as carriers to provide excellent loading sites and protection for small-molecule drugs. In addition, MOFs can be used to combine with a variety of therapeutic drugs, including chemotherapeutics drugs, photosensitizers, and radiosensitizers, to efficiently deliver drugs to tumor tissue and achieve desired treatment. There is hardly any review regarding the application of MOFs in hepatocellular carcinoma. In this review, the design, structure, and potential applications of MOFs as nanoparticulate systems in the treatment of hepatocellular carcinoma are presented. Systematic Review Registration: website, identifier registration number